^{2}+ bx + c = 0 form, where a, b and c are constants and ‘x’ is a variable. Now we discuss how to factor quadratic Polynomials:

We use following steps to factor a quadratic polynomials-

Step 1: First of all, we check constant number in a given Quadratic Equation like we have a quadratic equation x

^{2}+ 5x + 6 = 0, then we can find constant 6.

Step 2: After evaluation of constant, we find out all possible factors of that constants like we have 6 as a constant, then all possible factors of 6 is (1 * 6), (2 * 3) and (6 * 1).

Step 3: After all possible factors, now we check our second constant which is a multiple of ‘x’ like in above quadratic equation x

^{2}+ 5x + 6 = 0, we have a second constant 5, which is a multiple of ‘x’.

Step 4: Now we find one possible factor from all possible factor to make our second constant like in above quadratic equation x

^{2}+ 5x + 6 = 0, we have a possible factor (2 * 3), which make our second constant 5, which is an addition of 2 and 3,

x

^{2}+ 5x + 6 = 0,

=> x

^{2}+ (2 + 3)x + 6 = 0,

=> x

^{2}+ 2x + 3x + 6 = 0,

=> x(x + 2) + 3(x + 2) = 0,

=> (x + 2)(x + 3) = 0,

So, factors of x

^{2}+ 5x + 6 = 0 is (x + 2) and (x + 3).

Therefore we use these 4 steps for factoring a quadratic equation,like factor of x

^{2}+ 7x + 6 = 0 is (x + 1) and (x + 6).